Social Identities in the Policy Process of Authoritarian Systems - Johanna Hornung; Ilana Schröder; Nils C. Bandelow (Politische Vierteljahresschrift, 2022)
The integration of the social–psychological social identity approach to policy process research has recently generated new insights on policy-making. Empirical applications for established democracies and multilevel settings such as the European Union have identified five general types of social identities that are relevant for the preferences and behavior of policy actors and their stability and change over time. Social identities are based on joint memberships in social groups, such as organizations, demographic/biographical identities, sectors, locations, and informal opportunities for exchange (which may result in programmatic groups and identities). Some of these social groups, above all pluralistic interest associations and political parties, are directly related to the settings of embedded democracies. This article sheds light on the traveling capacity of the Social Identities in the Policy Process (SIPP) perspective by applying it to the Russian political system. An analysis of policy actors' social identities in two federal ministries shows that in autocracies, interest intermediation, legitimacy, and influence on policy processes run through professional and informal groups when competing organizations and democratic institutions are absent. The results indicate that the SIPP perspective is adaptable to policy processes in different contexts but that the importance of identity types varies. – – Die Integration des sozialpsychologischen Social-Identity-Ansatzes in die Policy-Forschung hat in jüngster Zeit zu neuen Erkenntnissen über die politische Entscheidungsfindung geführt. Empirische Anwendungen in etablierten Demokratien und Mehrebenensystemen wie der Europäischen Union haben fünf allgemeine Arten sozialer Identitäten identifiziert, die für die Präferenzen und das Verhalten politischer Akteure sowie deren Stabilität und Veränderung im Laufe der Zeit relevant sind. Soziale Identitäten basieren auf gemeinsamen Zugehörigkeiten zu sozialen Gruppen, wie Organisationen, demographischen/biographischen Identitäten, Sektoren, Orten und informellen Austauschmöglichkeiten (die zu programmatischen Gruppen und Identitäten führen können). Einige dieser sozialen Gruppen, vor allem pluralistische Interessenverbände und politische Parteien, stehen in direktem Zusammenhang mit den Rahmenbedingungen eingebetteten Demokratien. Dieser Artikel beleuchtet die Reichweite der Perspektive der Social Identities in the Policy Process (SIPP), indem sie diese auf das russische politische System anwendet. Eine Analyse der sozialen Identitäten von politischen Akteuren in zwei Ministerien der Russischen Föderation zeigt, dass in Autokratien Interessenvermittlung, Legitimität und Einfluss auf politische Prozesse über professionelle und informelle Gruppen laufen, wenn konkurrierende Organisationen und demokratische Institutionen fehlen. Die Ergebnisse weisen darauf hin, dass die SIPP-Perspektive auf politische Prozesse in verschiedenen Kontexten anwendbar ist, die Bedeutung der Identitätstypen jedoch variiert.
Keywords: 320; Health Policy; Environmental Policy; Russian Politics; Public Policy in Autocracies; Programmatic Action Framework (PAF); Gesundheitspolitik; Umweltpolitik; Politik in Russland; Öffentliche Politik in Autokratien